2018
DOI: 10.1080/14786419.2018.1508149
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory effects of pomegranate peel extracts on bovine mammary epithelial cells BME-UV1

Abstract: Pomegranate peel extracts (PPE) were tested for the first time on BME-UV1, a valid cellular model to study the bovine mammary epithelial metabolism, to evaluate the effects on the oxidative stress and inflammatory status. Based on the statistical analysis of MTT data, PPE at 0.1, 1.0 and 10 μg/mL resulted not cytotoxic after 24 h, 48 h and 7 days of treatment. At the same concentrations, PPE induced a reduction of ROS production elicited by the addition of hydrogen peroxide or lipopolysaccharide evidencing an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…Both high-molecular and low-molecular weight phenolic compounds are present. High-molecular weight phenols were α- and β-punicalagin with 146.9 ± 1.465 mg/g and 266.3 ± 1.687 mg/g, respectively; gallic acid, ellagic acid and granatin B were low-molecular weight phenols found into PPE as minor components, as published previously [42,43].…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Both high-molecular and low-molecular weight phenolic compounds are present. High-molecular weight phenols were α- and β-punicalagin with 146.9 ± 1.465 mg/g and 266.3 ± 1.687 mg/g, respectively; gallic acid, ellagic acid and granatin B were low-molecular weight phenols found into PPE as minor components, as published previously [42,43].…”
Section: Resultssupporting
confidence: 82%
“…While polyphenols are known to suppress inflammatory responses by supressing NF-κβ and mitogen-activated protein kinase (MAPK) signalling pathways [61], the underlying mechanism of action of these compounds are still not well understood. In our previous study, using a bovine mammary cell model [43], we observed anti-inflammatory activity by the same PPE used in the current study. We suggested that the observed anti-inflammatory activity of PPE could be related to a bioactive hydrolysable tannin, the punicalagin, that was present in high amounts (88.8%) in our extract in form of α and β isomers [43].…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations